2000
DOI: 10.1038/sj.bmt.1702526
|View full text |Cite
|
Sign up to set email alerts
|

CMV pneumonia in allogeneic BMT recipients undergoing early treatment or pre-emptive ganciclovir therapy

Abstract: Summary:The incidence, treatment and outcome of CMV interstitial pneumonia (CMV-IP) were reviewed in 139 consecutive allogeneic BMT patients undergoing extended CMV antigenemia surveillance and two different ganciclovir (GCV) strategies to control CMV infection. Nineteen cases of CMV-IP were reviewed, 16 of 63 patients (25.4%) who received early GCV treatment (ET) and three of 76 patients (3.9%) who received preemptive (PE) GCV therapy. In the ET group, the median time for occurrence of CMV-IP was 55 (range 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 11 publications
4
46
0
3
Order By: Relevance
“…10,11 Early diagnosis of CMV antigenemia using PCR and preemptive therapy with ganciclovir, especially in patients 'at risk', may help in reducing the risk of CMV disease. 12,13 The incidence of hepatitis B and hepatitis C seems to be similar to western data. 14,15 Reactivation and hepatic dysfunction due to hepatitis B or C was uncommon among transplant recipients.…”
Section: Discussionsupporting
confidence: 56%
“…10,11 Early diagnosis of CMV antigenemia using PCR and preemptive therapy with ganciclovir, especially in patients 'at risk', may help in reducing the risk of CMV disease. 12,13 The incidence of hepatitis B and hepatitis C seems to be similar to western data. 14,15 Reactivation and hepatic dysfunction due to hepatitis B or C was uncommon among transplant recipients.…”
Section: Discussionsupporting
confidence: 56%
“…All these observations confirm previous reported data about the value of the AG test to monitor the duration of therapy and mainly to prevent unnecessary use of GCV. 16,22,24 We also observed that 32.4% of the AG episodes (both first and recurrent episodes) did not require GCV treatment (AG Ͻ2 cells) and undesirable antiviral side-effects could be avoided. It is important to stress that we prepared the AG slides with 300 000 polymorphonuclear leukocytes while other groups usually prepare slides with 50 000 to 200 000 PMN.…”
Section: Discussionmentioning
confidence: 74%
“…A Cox proportional hazards model considering the same covariates as above was fitted to the data. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ganciclovir combined with high-dose Ig, but this standard has never been evaluated in a controlled study and more recent studies have questioned whether the addition of Ig improves outcome. 22 For patients with CMV disease other than pneumonia, the addition of Ig does not seem to be beneficial.…”
mentioning
confidence: 99%